Pengembangan Media Pembelajaran Berbasis Gimkit Materi Perkalian Kelas V Sekolah Dasar - Yuanta, Friendha; Suroso, Nur Listiana Dwi Hutami; Wulandari, Diah Ayu; Anggraini, Dwi Nadila; Hermawan, Nadya Sapta; Yosepin Betssy Tomasoa (Indo-MathEdu Intellectuals Journal, 2025)
This research focuses on the development of Gimkit-based quiz media that emphasizes the process of creative and collaborative learning. Gimkit is an online game that can create a fun classroom atmosphere and motivate students to learn in diversity materials. The type of research used in this study is Research and development (R&D) using the Multimedia Devolopment Life Cycle development model. The stages carried out are concept, design, material collecting, assembly, testing, and distribution. The data collection techniques used are observation, questionnaires, and tests, while the data analysis techniques use qualitative and quantitative data analysis techniques. Research on the development of Gimkit-based interactive quizzes showed the results of media and material validation with a percentage of 89% stating that the Gimkit application is suitable for use as a learning medium. Thus, this Gimkit makes it easier for educators and students to explain the material and receive the material clearly and the learning goals can be achieved.